Two single nucleotide polymorphisms in the caprine GnIH gene are associated with litter size - Xiaopeng An; Lijuan Bao; Jinxing Hou; Yueyu Bai; Xinyan Zhao; Yuxuan Song; Binyun Cao (Czech Journal of Animal Science, 2017)
Gonadotropin-inhibitory hormone (GnIH) can decrease luteinizing hormone and/or follicle-stimulating hormone levels in rat, mouse, sheep, and cattle by the direct suppression of gonadotropin-releasing hormone (GnRH). The present study investigated polymorphisms in the GnIH genes of two dairy goat breeds and their association with litter size. Single nucleotide polymorphisms (SNPs) g.1837C>G and g.3195G>A (GenBank Accession Nos. KR778885 and KR819142) were detected in the GnIH genes of Xinong Saanen and Guanzhong dairy goat breeds using DNA sequencing and polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). Furthermore, the g.1837C>G and g.3195G>A loci were closely linked in both breeds (r2 > 0.33). Association analysis showed that these SNPs had significant effects on the litter size of goats (P < 0.05). In both breeds, individuals with the CC/GG (g.1837C>G/g.3195G>A) genotype showed larger litter sizes in the second and average parities than individuals with the GG/AA genotype (P < 0.05). Known biochemical and physiological functions, along with our results, indicate that the CC/GG genotype may be used in marker-assisted selection to choose individuals with a larger litter size from both breeds.